REGULASI DAN PENGAWASAN FINTECH DI INDONESIA : PERSFEKTIF HUKUM EKONOMI SYARIAH - Muhammad Fachrurrazy; Dirah Nurmila Siliwadi (IAIN BONE, 2020)
Technology-based financial innovation has an important role to develop national economic, regulatory and surveillance controls haven’t completely protected against legal and illegal fintech breaches. This study aims to analyze government policies in monitoring and providing legal protection against conflict in fintech and sharia violations. Research show fintech arrangements and surveillance are currently on financial service authority (POJK) and Indonesian’s central bank regulations (PBI) as the main regulator, and then the Fatwa DSN-MUI and the council governors rule (PADG BI) as the fan regulator. Fintech surveillance regulations are currently not running optimal because current surveillance was applied to a pre-operational stage due to regulations and oversight barriers. Keywords: Fintech; Islamic economic law; Legal Protection; Surveillance.